Cisplatin versus cetuximab with definitive concurrent radiotherapy for head and neck squamous cell carcinoma: An analysis of Veterans Health Affairs data. Issue 3 (20th October 2018) - Bauml, Joshua M.; Vinnakota, Ravi; Anna Park, Yeun‐Hee; Bates, Susan E.; Fojo, Tito; Aggarwal, Charu; Di Stefano, Jessica; Knepley, Christina; Limaye, Sewanti; Mamtani, Ronac; Wisnivesky, Juan; Damjanov, Nevena; et al.
Abstract : Background: The addition of cisplatin or cetuximab to radiation therapy (RT) improves outcomes in comparison with RT alone in the nonoperative management of head and neck squamous cell carcinoma (HNSCC), but limited data exist for comparing these approaches. Using Veterans Health Affairs data, this study compared the outcomes of patients treated with RT plus cisplatin or cetuximab. Methods: Patients with stage III to IVb HNSCC who had been treated nonsurgically with RT and cisplatin or cetuximab from 2000 to 2016 within the Veterans Health Affairs system were identified. Patients were analyzed by the drug used in the first treatment cycle (intent to treat). Overall survival (OS) was compared by treatment group with Cox regression models, and propensity score (PS) methods were used to account for a treatment allocation bias. The risk of toxicities was determined, with logistic regression models fit into propensity‐matched cohorts. Results: A total of 4520 patients were included in the analysis with a median follow‐up of 3 years: 83% received cisplatin. Cisplatin patients were younger ( P < .001) and had fewer comorbidities ( P < .001). In an unmatched analysis, cetuximab was associated with inferior OS ( P < .001). After PS matching, cetuximab treatment remained statistically significantly associated with inferior OS (1.7 vs 4.1 years; hazard ratio, 1.61; 95% confidence interval, 1.44‐1.79; P < .001). These differences remained significant across all primary HNSCC subsites and in comparison with low‐ and high‐dose cisplatin. Conclusions: Cetuximab with RT yields inferior OS in comparison with cisplatin for the nonoperative management of stage III to IVb HNSCC. According to this study, cisplatin may be the most appropriate partner for RT in this setting. Abstract : The addition of cisplatin or cetuximab to radiation therapy improves outcomes in comparison with radiation therapy alone in the nonoperative management of head and neck squamous cell carcinoma, but limited data exist for comparing these approaches. In a propensity score–matched analysis of 4520 patients treated for head and neck squamous cell carcinoma within the Veterans Health Administration, cetuximab yields inferior overall survival in comparison with cisplatin.